Attribute Implications and Reverberations of the Japanese Foreign Policy for Technology and Innovation Business in Thailand - Yaninee Songkajorn; Somnuk Aujirapongpan; Watcharawat Promma; Kitikorn Dowpiset; Jaturon Jutidharabongse (Emerging Science Journal, 2022)
Economic growth can be defined by real gross domestic value and international imports and exports supported by technology and innovation. Currently, there are concerns about the level of international technological policy investment, despite having the capability to be macroeconomically and business-valuable. The main objective of this research is to study the attributions in relationships and associations between the policy implications of technological business (PITB) and the effort of technology and innovation acceptance capacity (TIAC), which influence capacity development and foresight to ensure effective Japanese foreign policies. This research has been fully justified through business policy receiving technology and innovation, the potential for technology and innovation adoption (PTIA) and innovation for firm performance (IFP) of Japanese joint venture companies in Thailand was examined. Fifty-seven companies were subjected to the structural equation model testing method. Data collection was conducted by the questionnaire and an in-depth interview with validity and reliability checked under 4 main latent variables: PITB, TIAC, PTIA, and IFP. All processing was performed with the ADANCO 2.2.1 program. The research found that PITB had a positive correlation and directly influenced PTIA and IFP unless it had an inverse correlation to TIAC and the relationship between TIAC and PTIA. It can serve as a guide for how to correctly carry out the principle of creating a new Japan's foreign policy in the future. Doi: 10.28991/ESJ-2022-06-03-09 Full Text: PDF